Functional roles of Phe12 of deacetyl-thymosin β4 in the impaired blastogenic response of uraemic T-lymphocytes - T. Abiko; H. Sekino (Mediators of Inflammation)
Phe12 of deacetyl-thymosin β4 is one of the structural essentials for restorative effect on the impaired blastogenic response of uraemic T-lymphocytes. In order to evaluate the functional roles of this phenyl group in the restorative effect on impaired T-lymphocytes, two analogues, [1- Nal12]deacetyl-thymosin β4 and [Cha12]deacetyl4 thymosin β4, were synthesized by a solid-phase method and evaluated for restorative effect on the impaired blastogenic response of uraemic T-lymphocytes. The results indicated that [1-Nal12]deacetyl-thymosin β4 which had a bulky naphthyl ring showed a stronger restorative effect than that of deacetyl-thymosin β4, but it was slightly weaker than that of [Phe(4F)12]deacetyl-thymosin β4. However, [Cha12]deacetyl-thymosin β4 showed no restorative effect on the impaired blastogenic response of uraemic T-lymphocytes.